Emotional Intelligence: As a booster of Personal Relationships in the Context of Nepali Society - Panta, Sunil; Adhikari, Tara Prasad (NPRC Journal of Multidisciplinary Research, 2025)
Background: Emotional intelligence (EI) plays a crucial role in shaping interpersonal relationships, particularly in collectivist societies like Nepal, where familial and social bonds are deeply valued. This article explores the influence of EI on personal relationships within Nepali society considering cultural factors, familial expectations, and socio-emotional dynamics. Through a review of existing literature and cultural analysis, the paper highlights how EI contributes to conflict resolution, marital satisfaction, social cohesion in Nepal; attempting to unfold how EI can be harness in socio-cultural context of Nepal. Methods: A qualitative approach was chosen to gain in-depth understandings, experiences, perceptions, and interpretations of emotional intelligence and how it influences their personal and professional interactions. In order to regulate and in-depth exploration of the topic- research aligns with three major theories of EI; Daniel Goleman’s Mix Model, Bar-On Mix Model and Mayer – Salovey ability-based model. Results: Study unfolds, emotional intelligence has a significant contribution to strengthen and improve the quality of personal relationships in Nepal. By emphasizing empathy, emotional regulation, and effective communication within the framework of Nepali cultural factors, EI helps individuals build deeper and more resilient bonds in both familial and community settings. The study replicates Emotional Intelligence as a booster to cultivate deep personal and social relationship. Conclusion: Study directs ability to balance emotional expression balancing cultural values are possible to individuals who possesses higher EI skills. Conflict settlement without breaking family and social structure has direct connection with sense of empathy and ability to indirect communication. Furthermore, stronger and intense interpersonal influence adheres following hierarchal structures where elder members are respected. In a society deeply rooted in collective values, familial ties, community harmony, and social respect are central; emotional intelligence enhances the ability to empathize and communicate effectively. It also discusses the methods and practices on how education programs can be helpful to harness EI to Nepali cultural contexts.